EVALUATION OF DULUTH COMPLEX ANORTHOSITIC SERIES (AS3) ZIRCON AS A U-PB GEOCHRONOLOGICAL STANDARD: NEW HIGH-PRECISION ISOTOPE DILUTION THERMAL IONIZATION MASS SPECTROMETRY RESULTS - Schmitz M.D.; Bowring S.A.; Ireland T.R. (My University, 2003)
U-Pb zircon geochronology is increasingly called upon to achieve the resolution of absolute time at the 0.1% to 1% level for rocks of Phanerozoic to Hadean age. Doing so requires accurate calibration of the several methods (conventional isotope dilution thermal ionization mass spectrometry [ID-TIMS], Pb evaporation, high-resolution ion microprobe [e.g. SHRIMP], and laser ablation inductively coupled plasma mass spectrometry [LA-ICPMS]) currently in use, in numerous laboratories, for the analysis of U and Pb isotopes in accessory minerals. Toward this end, the geochronological community would benefit from the establishment, distribution and widespread analysis of one or more standard reference materials. Among the candidates is natural zircon from the Duluth Complex anorthositic series of the Midcontinent Rift system of North America. These zircons, first dated by conventional ID-TIMS at 1099.1 ± 0.5 Ma, have been subsequently adopted as a geochronological standard by a number of high resolution ion microprobe facilities. A new and independent analysis of the systematics of a large set of single zircons (n = 27) from the same mineral separate yields indistinguishable 207Pb/206Pb, upper intercept, and U-Pb concordia dates for the AS3 zircons. The concordia date, based on a subset of 12 concordant and equivalent zircons, of 1099.1 ± 0.2 Ma (±1.2 Ma considering systematic uncertainties in Pb/U tracer calibration and U decay constants) is indistinguishable from previously published results. We further document the absence of inherited Pb in the AS3 zircons, and discuss strategies for avoiding certain domains within the AS3 zircons exhibiting small amounts of radiation-induced, surface and fracture-correlated, recent Pb loss. Although the AS3 zircons do not represent the ideal (and elusive) homogeneous closed U-Pb system, we conclude that these and similar zircons from the Duluth Complex anorthositic series can provide a suitable geochronological reference standard for numerous U-Pb zircon analytical methods, given appropriate preparation guided by the results of this study. Our high-precision data set also serves as a useful confirmatory test of the currently accepted U decay constants.
Keywords: Zircon